Use of functional magnetic resonance imaging in the evaluation of neural plasticity in macular degeneration - Bochnička, Jakub; Kremláček, Jan (Frontiers in Neuroscience, 2025)
This review evaluates the use of functional Magnetic Resonance Imaging (fMRI) to investigate brain plasticity in Age-Related Macular Degeneration (AMD). An analysis of studies utilizing fMRI methods identified three primary research approaches: task-based fMRI (17 studies), resting-state fMRI (4 studies), and population receptive fields (pRF) with population connective fields modeling (pCF; 3 studies). The review outlines the principles behind each fMRI methodology and summarizes the key functional and morphological findings. Results consistently demonstrated significant structural and connectivity reorganization in the brains of individuals with AMD, suggesting that the brain undergoes adaptive responses to sensory loss. Voxel-based morphometric findings, measuring the gray matter volume loss in visual cortex, further confirm these structural changes, which appear to correlate with altered functional connectivity. These insights underscore the intricate relationship between sensory deficits and cognitive function in AMD and emphasize the potential for targeted therapeutic interventions. FMRI emerges as a vital tool in group studies for understanding the neural underpinnings of AMD and its broader cognitive implications.